Ocean waves and their response to monsoon - RAY, TK (MAUSAM, 1986)
The arrival of southwest monsoon in the Indian seas, its onset over India, the break and withdrawal phases reflect the manifestations of mechanical energy on the water surface. An inverse relationship between sea surface temperature and swell heights has been explained. High period swells appear over the Arabian Sea before monsoon onset which die down after onset. Height of south Indian Ocean swells and the active monsoon over India have a direct relationship. And an attempt has been made to predict the height of waves by use of a simple regression equation.